When Inappropriate Use of Insulin is Dangerous: The Utility of C-Peptide Assay in the Era of Cardioprotective Antidiabetic Drugs - Volpe S (Dove Medical Press, 2021)
Sara Volpe, Cosimo Tortorella, Vincenzo Solfrizzi, Giuseppina Piazzolla Interdisciplinary Department of Medicine, University of Bari “Aldo Moro” Medical School, Bari, 70124, ItalyCorrespondence: Giuseppina PiazzollaInterdisciplinary Department of Medicine, University of Bari “Aldo Moro” Medical School, Policlinico, Piazza G. Cesare 11, Bari, 70124, ItalyFax +39 080 5478126Email giuseppina.piazzolla@uniba.itIntroduction: New antidiabetic drugs have simplified treatment regimens in patients with type-2 diabetes (T2D). More importantly, they have proven to reduce cardiovascular risk by lowering insulin-resistance, blood pressure and body weight, in addition to avoiding inappropriate insulin therapy, responsible for hypoglycemic episodes and weight gain. In this context, accurate assessment of the metabolic status of T2D patients becomes essential. The C-peptide assay is a simple but often overlooked test that can provide a fundamental contribution to the correct disease classification and optimal therapeutic management of diabetic patients.Clinical Case: We report the case of a 72-year-old patient, treated with insulin for 26 years after a diagnosis of type-1 diabetes (T1D), resulting in inadequate glycemia control and a severe evolution of cardiovascular complications. After an accurate evaluation of the clinical history, phenotype and laboratory data, including the determination of C-peptide serum levels, a diagnosis was made of T2D not T1D. Considering the patient’s very high cardiovascular risk and dysmetabolic profile, insulin therapy was discontinued and more appropriate therapy with dulaglutide and metformin was instituted. These overall therapeutic modifications yielded remarkable clinical advantages in terms of the glycometabolic profile, weight reduction, abdominal circumference and body mass index decrease, as well as a better quality of life, with complete resolution of the dangerous hypoglycemic episodes.Conclusion: In the era of new cardioprotective antidiabetic drugs, we believe the importance of the C-peptide assay should be re-evaluated in order to avoid misdiagnosis and to improve the therapeutic approach to T2D.Keywords: diabetes, metabolic syndrome, hypoglycemia, obesity, dulaglutide, quality of life